2018
DOI: 10.4102/phcfm.v10i1.1727
|View full text |Cite
|
Sign up to set email alerts
|

The pattern and characteristics of sexual assault perpetrators and survivors managed at a sexual assault referral centre in Lagos

Abstract: BackgroundThere has presumably been an increase in cases of sexual assault in Nigeria; however, accurate data on the characteristics of the survivors and perpetrators are not readily available in most cases.AimTo report the pattern and characteristics of sexual assault perpetrators and survivors managed at the Mirabel Centre, Lagos State University Teaching Hospital (LASUTH), Ikeja – a three-year review.MethodsA retrospective audit carried out in the sexual assault referral centre (SARC) – Mirabel Centre, LASU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
4
20
0
Order By: Relevance
“…These data highlight the need to tailor SV services to a generally young population. The age and sex distribution of SV and the details surrounding the incidents reported at our centre mirror reports from other studies and programmes within the country [20], and in other settings [21,22], and suggest similar patterns of vulnerability in most communities. Importantly, whereas males accounted for a small proportion overall—12% of cases—and similar studies have also reported a lower proportion of male survivors compared with females [23,24], over half were aged 11 years and below.…”
Section: Discussionsupporting
confidence: 78%
“…These data highlight the need to tailor SV services to a generally young population. The age and sex distribution of SV and the details surrounding the incidents reported at our centre mirror reports from other studies and programmes within the country [20], and in other settings [21,22], and suggest similar patterns of vulnerability in most communities. Importantly, whereas males accounted for a small proportion overall—12% of cases—and similar studies have also reported a lower proportion of male survivors compared with females [23,24], over half were aged 11 years and below.…”
Section: Discussionsupporting
confidence: 78%
“…It has been defined as any sexual act, attempt to obtain a sexual act, unwanted sexual comments or advances, or acts to traffic, or otherwise directed, against a person's sexuality using coercion, by any person regardless of their relationship to the survivor, in any setting, including but not limited to home and work. 1 This act is committed against someone without that person's consent. 1,2 It entails the use of physical force, coercion, deception or threat; and/or the involvement of a victim that is asleep, unconscious, under aged, mentally incapacitated or physically impaired as a result of voluntary or involuntary alcohol or drug consumption.…”
Section: Introductionmentioning
confidence: 99%
“…1 This act is committed against someone without that person's consent. 1,2 It entails the use of physical force, coercion, deception or threat; and/or the involvement of a victim that is asleep, unconscious, under aged, mentally incapacitated or physically impaired as a result of voluntary or involuntary alcohol or drug consumption. [3][4][5] Coercion can cover a whole spectrum of degrees of force.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations